Tubercular Mastitis in an Elderly Female: A Rare Entity - Jha, Manvendu; Singh, Hakam; Kaur, Amulyajeet (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Tuberculosis of the breast is a rare entity, especially in elderly females. Moreover, the disease is overlooked and misdiagnosed as malignancy or pyogenic abscess. Here we report a case of an elderly female who presented with a lump in her left breast which resembled malignancy. Fine needle aspiration cytology followed by histopathological examination confirmed the diagnosis of breast tuberculosis. Patient underwent excision of the lump followed by six months of anti tubercular therapy to which she responded well. Key words: breast; mastitis; tuberculosis